The dynamic relationship between blockchain technology adoption and supply chain performance based on the Chinese manufacturing industry - Dou, Yizhuo (2021)
In this era of rapid development of information technology, blockchain has received a lot of attention as an emerging technology. Currently, efforts are being made in the field of supply chain operations and management to try to incorporate blockchain technology to solve some complex supply chain problems. However, as blockchain is a new technology, there are few references in this area. Against this background, this thesis investigates the dynamic relationship between the adoption of blockchain technology and supply chain performance, thereby further bridging this gap. The researcher builds on the existing literature on blockchain and new technology adoption, as well as the supply chain performance literature. A model based on the Technology Acceptance Model (TAM) was also developed and empirically studied in the Chinese manufacturing industry. The researcher collected 182 questionnaires on blockchain adoption and analysed the responses using SmartPLS 3.0. The final results of the study obtained concluded that the adoption of blockchain technology can improve supply chain performance to some extent. The findings of this thesis show that technical context, organisational context and environmental context are critical to the adoption of blockchain technology, while supply chain performance is influenced by transparency and supply chain visibility. These findings have both theoretical and practical implications. The model in this thesis enriches the existing literature in the field of blockchain technology and supply chains and provides a new way of thinking for future research by scholars and experts.